When do we have borrower or credit volume rationing in competitive credit market with imperfect information? - Daniel Kraus (Universität Rostock, Institut für Volkswirtschaftslehre, 2010)
This paper examines the conditions for credit volume or borrower rationing in a competitive credit market in which the project characteristics are private information of the borrowers. There can only be credit volume rationing if the higher-risk credit applicants have a higher return in the event of a project success than the lower-risk credit applicants. Then the higher-risk borrowers are not rationed and obtain the social efficient credit volume. If the incentive compatibility constraint of the higher risk borrowers is binding, the lower-risk borrowers are credit volume rationed such that the constraint holds as an equation. If credit volume rationing is not sufficient to separate the borrower types, there is additionally a rationing of the low-risk borrowers. If the low-risk borrowers prefer a pooling to a separating contract, then there will not be a Cournot-Nash separating equilibrium, but a Wilson and a Grossmann pooling equilibrium.
Keywords: D82; G21; 330; Credit rationing; Credit Size; Loan; Asymmetric Information; Adverse Selection; Non-linear optimization; Kreditrationierung; Kreditmarkt; Asymmetrische Information; Adverse Selektion; Theorie